1876-77 N.C. Sess. Laws 162-163 - (:unkn) unknown (My University, 1875)
Ch. 104, §§ 1-2: If any person shall be found off of his own premises, within the county of Alleghany, having concealed about his person a pistol, bowie-knife, dirk, dagger, slung-shot, loaded cane, or brass or iron knuckles, or other deadly weapon of a like kind, such person shall be deemed guilty of a misdemeanor, and, upon conviction thereof, shall be fined or imprisoned at the discretion of the court.
Keywords: CARRY - CONCEALED